THE GENERATION OF GAS OVERPRESSURE IN VOLCANIC ERUPTIONS - Massol H.; Jaupart C. (My University, 1999)
Observations of natural eruption products show that different parts of a single magma batch may experience different degassing histories during ascent in a volcanic conduit. In non-explosive eruptions, lava issuing from a volcanic vent may contain overpressured gas bubbles. These important features of volcanic eruptions cannot be accounted for by existing flow models, which rely on simplifying hypotheses for the relationship between pressures in the gas phase and in the bulk flow. Volcanic flows involve highly compressible material which undergoes large viscosity variations as degassing proceeds. We show that these properties may lead to large gas overpressures in erupting lava. The magnitude of this overpressure depends on the initial volatile content of magma and is largest for relatively volatile-poor magmas, due to the extreme viscosity variations at water contents less than 1 wt%. We develop a simple analytical model to illustrate the main features of compressible viscous flows: (1) at any level, gas pressure is larger near the conduit axis than at the walls, (2) gas overpressure is an increasing function of mass discharge rate.
Keywords: VISCOSITY; COMPRESSIBILITY; EXPLOSIVE ERUPTIONS; MAGMAS; VISCOUS MATERIALS; LAVA FLOW